Bond strength of orthodontic brackets to temporary crowns: In vitro effects of surface treatment - Neal B Kedia; Bhushan Bangar; Srerama Janardhana Rao; Siddharth Swarup; Deepak Singh; Drashti K Chikhalia (Wolters Kluwer Medknow Publications, 2023)
Background: To evaluate bond strength of orthodontic brackets to temporary crowns. Materials and Methods: A bis-acrylic composite was used to create a total of 25 discs, which were then divided into five groups based on how their surfaces were treated with black, blue, green, and sandblasted diamond burs, in addition to a control group. Software called SPSS was used to analyze the outcome. Results: The average pressures measured for the green bur, black bur, and sandblasting, respectively, were 12.05 MPa, 12.87 MPa, and 19.25 MPa. Comparing the control and blue groups, a substantial variation in shear bond strength was only noticed with reference to sandblasting. Conclusion: The binding strength of orthodontic brackets is increased by sandblasting temporary crowns.